2020
DOI: 10.1021/acs.energyfuels.0c02577
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonoxidized Sulfur Species on Elemental Mercury Removal by SO2 Activated Petroleum Cokes

Abstract: High-sulfur petroleum coke is potentially one of the most promising materials for developing efficient and low-cost sorbents for Hg0 removal from flue gas. In this study, three distinct SO2-activated high-sulfur petroleum cokes were prepared at 650–850 °C via different sulfurization protocols, including SO2-impregnated petroleum coke (PC-S), SO2-impregnated coke produced with an additional reductive heat-treatment process in N2 (PC-NS), and SO2-impregnated coke prepared with the presence of SO2 in the gas duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Xiao et al [ 38 ] found that over 90% of sulfur was thiophene and organic sulfide (R-Sn-R), and the rest 10% was in the form of oxides, such as sulfate. She et al [ 48 ] analyzed the XPS spectra which suggested that more than 94.40% of the inherent sulfur existed as thiophene. Meanwhile, sulfoxide, sulfone, and sulfate were detected in very small quantities.…”
Section: The Effect Of the Evolution Of Functional Groups On Hg ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Xiao et al [ 38 ] found that over 90% of sulfur was thiophene and organic sulfide (R-Sn-R), and the rest 10% was in the form of oxides, such as sulfate. She et al [ 48 ] analyzed the XPS spectra which suggested that more than 94.40% of the inherent sulfur existed as thiophene. Meanwhile, sulfoxide, sulfone, and sulfate were detected in very small quantities.…”
Section: The Effect Of the Evolution Of Functional Groups On Hg ...mentioning
confidence: 99%
“…Although this research could not carry on a mercury removal test, the transformation of the S-containing groups and the released S-containing gas components give the help for further modification of HSPC. It is noted that the released S-containing gas during pyrolysis, such as SO 2 , was selected to activate HSPC [ 48 ].…”
Section: The Effect Of the Evolution Of Functional Groups On Hg ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Chlorine can enhance the adsorption and fixation of mercury in coal-fired fly ash, while the content of chlorine in coal in China is generally low, limiting the amount of Hg 0 in flue gas [18,19]. Activated carbon injection is considered the best available and promising technology for controlling mercury emissions from coal-fired power plants [20]. However, the high cost of activated carbon makes this technology economically unfavorable [20].…”
Section: Introductionmentioning
confidence: 99%